ANALISIS KARAKTERISTIK MEKANIK DAN HIDROLIK BETON BERPORI DENGAN SUBSTITUSI LIMBAH GRANIT DAN PENAMBAHAN METAL SWARF - Kholis Hapsari Pratiwi; Oktavia Kurnianingsih; Akhillah Kurniasari; Cindy Aulia Santoso; Desh Azira Rossanti (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2026)
Pervious concrete is an innovative construction material that allows water to infiltrate directly into the ground, supporting natural drainage systems and enhancing environmental sustainability in urban areas. Granite waste is utilized as a partial substitute for coarse aggregate to improve concrete efficiency while reducing the environmental impact of marble industry waste. Metal swarf is added as an innovative reinforcing material to enhance compressive strength and durability by improving load distribution and reducing crack propagation potential. This study evaluates the influence of varying cement content (467 kg/m³ and 600 kg/m³) on the compressive strength and permeability of pervious concrete, using a 30% substitution of granite waste as coarse aggregate and the addition of metal swarf (7.5%–13%) with lengths ranging from 0 to 5 cm. The research was conducted experimentally in the laboratory without the use of fine aggregates, with a target compressive strength of 17 MPa and a slump of 0 cm. Results showed that the optimal compressive strength was achieved with a higher cement volume of 600 kg/m³, reaching 17.41 MPa at 28 days (sample BI12). The highest permeability, 0.37 cm/s, was found in BI6 (467 kg/m³ cement and 13% metal swarf), while the lowest, 0.20 cm/s, occurred in BI9 (600 kg/m³ cement and 9.5% metal swarf). It can be concluded that variations in the proportion of cement and metal swarf significantly affect the performance of pervious concrete. A balanced material composition is essential to optimize its properties. This concrete is suitable for light infrastructure applications such as residential roads, paving blocks, parking areas, green open spaces, and sports fields. Abstrak Beton berpori merupakan material konstruksi inovatif yang memungkinkan air meresap langsung ke dalam tanah, mendukung sistem drainase alami dan keberlanjutan lingkungan di kawasan urban. Limbah granit dimanfaatkan sebagai substitusi agregat kasar untuk meningkatkan efisiensi beton sekaligus mengurangi dampak lingkungan dari limbah industri marmer. Sementara itu, bubutan besi (metal swarf) ditambahkan sebagai bahan inovatif untuk meningkatkan kuat tekan dan ketahanan beton dengan memperbaiki distribusi beban serta mengurangi potensi keretakan. Penelitian ini mengevaluasi pengaruh variasi jumlah semen (467 kg/m³ dan 600 kg/m³) terhadap kuat tekan dan permeabilitas beton berpori, dengan substitusi 30% limbah granit dan tambahan bubutan besi (metal swarf) sebesar 7,5%–13% (panjang 0–5 cm). Penelitian dilakukan secara eksperimental di laboratorium tanpa agregat halus, dengan target kuat tekan 17 MPa dan slump 0 cm. Hasil menunjukan bahwa kuat tekan optimal beton diperoleh pada campuran dengan volume semen yang lebih tinggi, yaitu 600 kg/m³ 17,41 MPa (BI12) pada umur 28 hari. Permeabilitas tertinggi sebesar 0,37 cm/detik diperoleh pada BI6 (semen 467 kg/m³ dan 13% bubutan besi), dan terendah 0,20 cm/detik pada BI9 (semen 600 kg/m³ dan 9,5% bubutan besi). Hal ini dapat disimpulkan bahwa variasi proporsi semen dan bubutan besi berpengaruh signifikan terhadap beton berpori. Keseimbangan komposisi material penting untuk mengoptimalkan performa beton berpori. Beton ini sesuai untuk infrastruktur ringan seperti jalan lingkungan, paving block, area parkir, ruang terbuka hijau (RTH), dan lapangan olahraga.